Development of laboratory scale model of field automatic water control system with sheetpipe technology. Issue 1 (October 2021) - Saptomo, S K; Arif, C; Suwarno, W B; Agustina, H; Putra, A G; Wiranto,; Tamura, K; Matsuda, H; Setiawan, B I
Abstract: In this study, a 2mx2mx0.5m box is modeled, filled with soil having a thickness of 40 cm rice fields and sheet pipe subsurface drainage installed 30 cm below the surface. The sheet pipe is connected to the air duct and reservoir upstream and the drainage outlet pipe downstream. Automation of the water level control in the reservoir is done utilizing a digital controller which has been programmed and connected to a water level sensor and a solenoid valve. If the water level is detected falls below the minimum threshold, the controller will open the solenoid valve and flow water to the reservoir until the specified level. This system is connected to the server via wireless internet, data monitoring and control settings can be done by the user via a dashboard in an internet browser. The test was carried out for approximately 3 months with rice planting and un-inundated irrigation. The test results show that the system has been able to function in remote monitoring and regulation of the controller, automatic irrigation operations, and water supply in the land as needed in the rice planting experiment with the control error of 2.6 cm.